A case study on effect of air movement at train platform / Syed Haziq Saggaff Syed Hood, Hazril Sherney Basher and Mohd Hafizal Mohd Isa - Syed Hood, Syed Haziq Saggaff; Basher, Hazril Sherney; Mohd Isa, Mohd Hafizal (2022)
Nowadays, train station is a common transportation used by people and gradually increases in popularity due to walkable city approach. Comfortability at the platform are important as all passenger use the space and it is improving for user convenient, safety and security according to location needs. Under ventilation aspect, air movement are important because the tunnelling effect of present platform design have to meet passenger comfort and standard. Issue such as crowded people, train movement, heat, dust and air pollution by train adding with the pandemic virus Covid-19 create new opportunities of study on air movement. The methodology of investigation is field measurement conducted in KL Sentral using Extech 45160 3 in 1 Anemometer and questionnaire survey with 21 questions answered by 70 respondents. Based on the method, this paper analyses and comprehensively evaluates the ventilation indicator of thermal performance of KTM KL Sentral station platform. The results show an average air velocity of 0.05 - 0.16 m/s, an average air temperature of 30.75 - 33.03 ℃, and an average humidity of 62.63 - 72.30%. Most of the platform users hardly accept the air velocity and air temperature, while 60% of users agreed that the relative humidity is dry or a little dry. The acceptability range for user at the train platform were found to be for air velocity is more than 0.15 m/s, indoor air temperature is 26℃ and relative humidity is 65-75%.